Perinatal outcomes of Aboriginal women with mental health disorders - Adane, A.A.; Shepherd, Carrington; Walker, R.; Bailey, Helen; Galbally, M.; Marriott, R. (2023)
Objective: Maternal mental disorders have been associated with adverse perinatal outcomes such as low birthweight and preterm birth, although these links have been examined rarely among Australian Aboriginal populations. We aimed to evaluate the association between maternal mental disorders and adverse perinatal outcomes among Aboriginal births. Methods: We used whole population-based linked data to conduct a retrospective cohort study (N = 38,592) using all Western Australia singleton Aboriginal births (1990–2015). Maternal mental disorders were identified based on the International Classification of Diseases diagnoses and grouped into six broad diagnostic categories. The perinatal outcomes evaluated were preterm birth, small for gestational age, perinatal death, major congenital anomalies, foetal distress, low birthweight and 5-minute Apgar score. We employed log-binomial/-Poisson models to calculate risk ratios and 95% confidence intervals. Results: After adjustment for sociodemographic factors and pre-existing medical conditions, having a maternal mental disorder in the five years before the birth was associated with adverse perinatal outcomes, with risk ratios (95% confidence intervals) ranging from 1.26 [1.17, 1.36] for foetal distress to 2.00 [1.87, 2.15] for low birthweight. We found similar associations for each maternal mental illness category and neonatal outcomes, with slightly stronger associations when maternal mental illnesses were reported within 1 year rather than 5 years before birth and for substance use disorder. Conclusions: This large population-based study demonstrated an increased risk of several adverse birth outcomes among Aboriginal women with mental disorders. Holistic perinatal care, treatment and support for women with mental disorders may reduce the burden of adverse birth outcomes.